2021
DOI: 10.1016/j.sjbs.2021.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of MYB transcription factors for cuticular wax biosynthesis and drought stress tolerance in Helianthus annuus L.

Abstract: Sunflower is an important oil-seed crop in Pakistan, it is mainly cultivated in the spring season. It is severely affected by drought stress resulting in lower yield. Cuticular wax acts as the first defense line to protect plants from drought stress condition. It seals the aerial parts of plants and reduce the water loss from leaf surfaces. Various myeloblastosis (MYB) transcription factors (TFs) are involved in biosynthesis of epicuticular waxes under drought-stress. However, less information is available for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…MuMYB96 transcript levels were significantly increased in multigene transgenic plants and also resulted in the overexpression of its downstream target genes KCS6 and KCR1, supporting their role increased cuticular wax accumulation. Earlier drought induced expression of MYB96 and its downstream genes KCS6 and KCR1 were reported in response to drought stress (Lee et al, 2016;Zhang et al, 2019;Lewandowska et al, 2020;Ahmad et al, 2021;Huang et al, 2022) (Figure 8).…”
Section: A B Figurementioning
confidence: 84%
“…MuMYB96 transcript levels were significantly increased in multigene transgenic plants and also resulted in the overexpression of its downstream target genes KCS6 and KCR1, supporting their role increased cuticular wax accumulation. Earlier drought induced expression of MYB96 and its downstream genes KCS6 and KCR1 were reported in response to drought stress (Lee et al, 2016;Zhang et al, 2019;Lewandowska et al, 2020;Ahmad et al, 2021;Huang et al, 2022) (Figure 8).…”
Section: A B Figurementioning
confidence: 84%
“…One study revealed that most AP2/ERF transcription factors exhibit root-specific expression [ 112 ], which is similar to the results of our study, in which we detected a greater number of ERF transcription factors in roots than in leaves. Some recent studies have shown that some MYB genes in sunflowers are highly expressed under drought stress [ 113 ]. According to our results, MYB genes were more downregulated in the leaves than in the roots.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors (TFs) are pivotal modulators of crop improvement, and facilitate the activation of regulatory mechanisms in plants [ 22 , 34 ]. The promoter region of cotton GPDH genes, contains numerous transcription factor binding sites, including multiple MYB-associated transcription factor recognition sites, and MYB has been shown to be associated with the abiotic stress response in plants in several studies [ 35 , 36 , 37 , 38 ]. Likewise, the hormone constitutes one of the important factors in affecting cotton growth and development, and abundant stress-related hormone response cis-elements further illustrate the potential of GPDH in coping with abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%